Sanksi Hukum Pelaku Tindak Pidana Kekerasan pada Anak yang Semakin Merajalela di Indonesia - Novienlita, Maria (Indra Institute Research & Publication, 2024)
Children are a gift from Allah SWT who must be looked after and educated as best as possible. Apart from that, children are the hope of the nation so children must be protected and not made objects of violence. In this writing the author uses two methods, namely the library method and also internet searching, where the data obtained comes not only from book sources but also the internet, which of course contains a lot of information related to the author's research. Where the formulation of the problem in this paper is (1) what is meant by violence against children, (2) what are the legal sanctions for perpetrators of violence against children and examples of cases, (3) what are the obstacles for investigators in handling cases of violence against children in Indonesia, (4) what is the role of the government in preventing violence against children in Indonesia, and the conclusions are (1) violence against children is all forms of violence against children committed by those who should be responsible for the child or those who have power over the child who should be trustworthy , for example parents, close family and teachers, (2) criminal sanctions for perpetrators of violence against children can be punished with imprisonment for three years and six months and/or a fine of up to Rp. 72,000,000, and an example of a case of violence against children occurred in Jambi where the mother had the heart to attach an iron to her child who had just come home from school, this was triggered by the mother being emotional with her husband because he was given little spending money. (3) the obstacles faced by law enforcers are the difficulty of obtaining information from victims because the victims have a high level of trauma and fear, there are no articles that regulate certain sexual violence against children, there is intimidation from the perpetrator and a lack of support from the community in the environment. around the victim's house, (4) and the government's role in the process of preventing violence against children is through various wise policies, strengthening the child protection system, public education and strict law enforcement and the government can create a safe environment and support for children. so that they can grow and develop without violence and carry out campaigns or outreach and education to parents about the impact of violence on children.